Rough Draft of History : A Century of US Social Movements in the News - Amenta, Edwin, 1957-; Caren, Neal (Book collections on Project MUSE., 2022)
"A comprehensive account of the media's coverage of social movements in the United StatesA new view of twentieth-century US social movements, Rough Draft of History examines how national newspapers covered social movements and the organizations driving them. Edwin Amenta and Neal Caren identify hundreds of movement organizations, from the Women's Christian Temperance Union to Occupy Wall Street, and document their treatment in the news. In doing so, Amenta and Caren provide an alternative account of US history from below, as it was refracted through journalistic lenses.Iconic organizations in the women's rights, African American civil rights, and environmental movements gained substantial media attention. But so too did now-forgotten groups, such as the German-American Alliance, Committee to Defend America by Aiding the Allies, and Peace and Freedom Party. Amenta and Caren show why some organizations made big news while others did not, why some were treated well while others were handled roughly. They recover forgotten stories, including that of the Townsend Plan, a Depression-era organization that helped establish Social Security. They also reveal that the media handled the civil rights movement far more harshly than popular histories recount. And they detail the difficulties movements face in today's brave new media world.Drawing from digitized newspapers across a century and through to the present, Rough Draft of History offers insights for those seeking social and political change and those trying to make sense of it"--